The Myth of al-Ghazālī and Islamic Decline: A Historical Clarification and Review - Mahmuluddin Mahmuluddin (TSAQAFAH, 2024)
This study aims to investigate the causes of the decline of scientific tradition in the Islamic world, considering three conventional theses proposed by liberal Muslim and Western intellectuals: internal and external factors. The first thesis attributes the decline to al-Ghazālī’s supposed rejection of science as depicted in his Tahāfut al-falāsifa (The Incoherence of the Philosophers), followed by the Islamic world, leading to its decline. Meanwhile, the second thesis identifies the Mongol invasion of Baghdad in 1258 as the main cause. The last thesis stated that the decline causes by the banning of printing press by Ottoman Empire specifically at the time of Sultan Bayezid II in 1485 and Selim I in 1515. Applying historical analysis method, this research seeks to uncover the truth behind these theses by examining relevant literature. Surprisingly, the results contradict the initial assumptions. The first thesis is rejected as al-Ghazālī did not reject science but rather supported it. His views were misunderstood by his detractors. Additionally, after the al-Ghazālī era, science and philosophy continued to thrive in the Islamic world. Similarly, the second thesis is also refuted as science and philosophy persisted and developed despite the Mongol invasion of Baghdad. Within a year of the invasion, the Maragha Observatory was established under the guidance of Nas}īr al-Dīn al-T}ūsī, a renowned Muslim scientist. This observatory became a global scientific hub, making significant contributions to mathematics and astronomy. The final proposition is similarly dismissed, as the Ottoman Sultans did not categorically dismiss the concept of the printing press; instead, they opted for a temporary restriction on its utilization within particular societal segments. This action was motivated by the apprehension that unrestricted access to the printing press among specific groups could possibly result in adverse political and economic outcomes for the larger Muslim community. To offer an alternative perspective, this study utilizes Janet Abu-Lughod’s European hegemonic approach, stemming from Immanuel Wallerstein’s world-system theory. By applying this approach, the author argues that the waning of scientific advancement in the Islamic world can be traced back to modern Western hegemony and its dominance over the Muslim realm.